Shariah governance for Islamic microfinance Industry = Tadbir urus bagi industri kewangan mikro Islam - Tijani, Ibrahim Musa; Hassan, Rusni; Ab. Nasir, Wan Amir Shafiq (IIUM Press, International Islamic University Malaysia, 2020)
Microfinance is a growing industry that caters to various forms of financing for the financially underprivileged segment of any society. The microfinance industry aims to provide financial assistance to the poor, small and medium enterprises (SMEs), micro-entrepreneurs, and other financially marginalized segments. Although the microfinance industry continues to assist numerous people, its traditional mechanism of financing, interest-based deposits and interest-bearing loans (riba), is not permissible according to the Muslim belief. As an alternative, Islamic Microfinance was established to cater to the Muslim community. Islamic microfinance is increasingly becoming an effective mechanism to tackle poverty, inequality and provide financing to micro-entrepreneurs and small and medium enterprises (SMEs) in Muslim countries. However, for the integrity and credibility of the Islamic microfinance industry there is a need for good governance and regulations. Governance and regulation are still a major concern for both microfinance and Islamic microfinance. An added aspect of governance that is peculiar to the Islamic microfinance is Shariah governance. This paper will examine the possible means to establish Shariah governance for the Islamic microfinance industry. The paper is conceptual in nature and is based on literature review to support the theory of the research.***************************************************** Pembiayaan mikro adalah industri yang berkembang serta memenuhi pelbagai bentuk pembiayaan untuk segmen masyarakat yang kurang bernasib baik. Industri pembiayaan mikro bertujuan untuk memberikan bantuan kewangan kepada golongan miskin, perusahaan kecil dan sederhana (PKS), pengusaha mikro, dan segmen lain yang terpinggir dari segi sektor kewangan yang utama. Walaupun industri pembiayaan mikro banyak membantu golongan tersebut, tetapi mekanisme pembiayaan tradisional yang diamalkan adalah berdasarkan deposit serta pinjaman dengan faedah (riba) yang tidak dibenarkan menurut Islam. Sebagai alternatif, pembiayaan mikro Islam ditubuhkan untuk memenuhi keperluan masyarakat Islam. Pembiayaan mikro Islam menjadi mekanisme yang berkesan untuk mengatasi kemiskinan, ketidaksamaan dan menyediakan pembiayaan untuk pengusaha mikro dan perusahaan kecil dan sederhana (PKS) di negara-negara Islam. Namun, untuk menaiktaraf integriti dan kredibiliti industri kewangan mikro Islam, peraturan mengenai tadbir urus yang baik adalah diperlukan. Secara umumnya, peraturan mengenai tadbir urus yang baik masih menjadi perhatian utama bagi kedua-dua sektor pembiayaan mikro dan pembiayaan mikro Islam. Walaubagaimanapun, bagi pembiayaan mikro Islam terdapat tambahan khusus di dalam aspek tadbir urus mereka iaitu aspek pematuhan Syariah. Kertas ini akan mengkaji cara untuk mewujudkan tadbir urus Syariah bagi industri kewangan mikro Islam. Kertas ini bersifat berbentuk konseptual dan menggunapakai tinjauan literatur untuk menyokong teori penyelidikan yang dilakukan.